(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Human Resource Accounting (HRA) involves accountingfor expenditures related to human resources, as assets as opposed totraditional accounting which treats these costs as expenses that reduce profit.Interest and contributions to growth in HRA have been evident in a number ofcountries. The strong growth of international financial reporting standards(IFRS) is an indication that the environment for international financialaccounting is one that potentially encourages the consideration of alternativemeasurement and reporting standards and lends support to the possibility thatfuture financial reports may include nontraditional measurements such as thevalue of human resources using HRA methods.